EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PROBLEM SOLVING TERHADAP HASIL BELAJAR DAN KESIAPSIAGAAN MENGHADAPI RISIKO BENCANA TSUNAMI DI PACITAN - Dian Widya Mardiana; Mohammad Gamal Rindarjono; Chatarina Muryani (Universitas Sebelas Maret (UNS), 2017)
ABSTRACTThis study aims: (1) to distinguish the positive difference of students’ learning result in the application of Problem Based Learning, Problem Solving and Conventional learning models; (2) to distinguish the positive difference of students’ preparedness in the application of Problem Based Learning, Problem Solving and Conventional learning models; (3) to identify that the learningresult of students in the application of Problem Based Learning model is more effective than Problem Solving learning model; (4) to identify that the preparedness of students in the application of Problem Based Learning model is more effective than Problem Solving learning model; (5) to find out that the learning result of students in the application of Problem Solving learning model is more effective than Conventional learning model; (6) to find out that the preparedness of students in the application of Problem Solving learning model is more effective than Conventional learning model; (7) to pinpoint that the learning result of students in the application of Problem Based Learning model is more effective than Conventional learning model; (8) to pinpoint that thepreparedness of students in the application of Problem Based Learning model is more effective than Conventional learning model. The method of the study used is quasi experimental. Samples are taken at random or by using simple random sampling technique, which are X IIS class 1, 2, and 4. Data collection technique used is test item and questionnaire. Hypothesis testing is done by the useof One-Way ANOVA and further testing is done by the use of Tukey test to identify the effectiveness of the three learning models. The results of research using One-Way ANOVA is F(3,122) > F(3.11) , H1 accepted, there is a positive difference of the students leraning results in the application of Problem Based Leraning, Problem Solving, and Conventional. Then, in the preparedness of students, the results showed F(3,501) > F(3.11), H1 is accepted, there is a positive difference of the students preparedness in the application of Problem Based Leraning, Problem Solving, and Conventional. Tukey test to students lerning results variable, the mean Problem Based Learning is 19.34, ProblemSolving is 17.93, Conventional is 18.93. On students preparedness variable, Problem Based Learning is 58.45, Problem Solving is 58.38, Conventional is 55.97.Key words: Problem Based Learning, Problem Solving, Learning Result, Students Preparedness